Some Reflections on the Benefits of the Professional Development Training Course "With Education to Plurilingualism" Managed through the Erasmus Plus Program - Birova, Jana; Klinka, Tomáš (Journal of Education Culture and Society, 2024)
Aim. The aim of the research was to find out and confirm the benefits of the professional development training course for language teachers managed thanks to the Erasmus Plus scheme. Methods. We used the evaluative form of the questionnaire and mathematical methods. The results represent the number of participants and the scale they agree with the statements.Results. 29 teachers evaluated two training internships in France, in Francophonia and Nice, and two internships in Slovakia. The third internship was provided by the European Center for Modern Languages ​​based in Graz on the topic of the Framework of reference for pluralistic approaches. The fourth training was focused on etwinning and the ESEP platform. The overall quality and satisfaction rating out of 5 points was 4.9.Conclusions. Thanks to Erasmus Plus, we facilitated a high-quality exchange of knowledge by incorporating innovative techniques, methods, and tools, which were promptly integrated into teaching practices. This collaboration significantly enhanced the partnership between schools and educators. As a result, teachers gained access to exceptional methodologies and approaches, which they applied in classrooms throughout Slovakia.